OSTEO-ODONTO-KERATOPROSTHESIS: AN INNOVATIVE APPROACH BETWEEN DENTISTRY AND OPHTHALMOLOGY IN VISUAL REHABILITATION - dos Santos, Pedro Guimarães Sampaio Trajano; de Ataíde Filho, Ailton Coelho; Cunha, Rodolfo Scavuzzi Carneiro; de Freitas, William Jose Lopes; Prosini, Priscila; Alves, Josué; do Nascimento, Alexandre Batista Lopes; Rodrigues, Verônica Maria de Sá; Cavalcanti, Maria Tereza Moura de Oliveira; de Menezes, Maria Regina Almeida; de Araujo, Luciane Farias; Travassos, Rosana Maria Coelho; et al. (ARACÊ, 2025)
Objective: The objective of this narrative literature review article is to address a rare and innovative technique capable of restoring vision to blind patients, through the visual prosthesis called ‘’ Osteo-Odonto-Keratoprosthesis ’’. Methodology: Therefore, searches were made in databases in order to acquire this content. The searches were carried out in the following databases: The Cochrane Library; PubMed; Science Direct; Scielo; PROSPERO in conjunction with Google Academy Results: Studies have shown that Osteo-Odonto-Keratoprosthesis is an innovative way of restoring vision to a blind patient, this occurs through the surgical removal of a tooth from the patient, where it will serve as support for the creation of an artificial cornea, a technique in which the tooth is prepared in a rectangular shape with a hole in the center, where a plastic optical lens will be positioned that will later give rise to a new functional cornea. Conclusion: This innovative technique consists of restoring vision, is innovative and has great potential, even though it is complex, and has a well-defined technique, which already has existing cases of patients who had their vision restored through this technique. However, it is clear that in each case, it is necessary to analyze whether this technique is possible to be performed on the patient or not, considering that it is necessary for the patient to have teeth, and that they have to be in adequate conditions, so that they can be removed and used in this technique, which sometimes does not occur, especially when the patient is elderly.